The molecular genetics of human complement C4: implications for mapping MHC disease susceptibility genes - Puschendorf, Mareike (Curtin University, 2003)
The Major Histocompatibility Complex (MHC) is a gene-dense region located on the short arm of chromosome 6 (6p21.31). This region contains the highly polymorphic HLA genes as well as many other genes with immunological and non-immunological function. The susceptibility genes of many human disorders have been mapped to genes within the MHC. However, the genes themselves and indeed the locations of the genes, for many of the disorders, remain a mystery. This is a result of the high degree of linkage disequilibrium (LD) that exists between loci within the MHC. The high LD is explained by the genomic structure of the MHC. The MHC contains several blocks of DNA within which recombination is extremely rare, whereas the boundaries of the blocks are defined as "hotspots" of recombination. Most disease association studies have used the highly polymorphic HLA class I and class II genes which are separated by an, as yet, undefined number of blocks and several hundred kilobases of DNA. The MHC gamma block resides in the central region of the MHC between the blocks that contain the HLA class I and class It genes. As such, typing for polymorphisms in the gamma block is critical for MHC disease gene mapping studies. The gamma block contains approximately 20 known genes including the complement C4 genes. The gamma block can contain between I and 3 tandemly arranged C4 genes. The C4 protein exists as either the C4A or C413 isotype and is polymorphic with up to 40 allotypes being reported. However, the majority of Caucasian haplotypes can be explained by the common C4A3 / C4B1 or C4AQ0 / C4B1 complotypes with the remaining haplotypes explained by just a few other complotypes. For this reason, and because C4 allotyping is a technically difficult procedure, C4 allotyping is rarely used in MHC disease association studies.The molecular heterogeneity of human C4 genes has not been extensively studied. However, the C4A3 and C4131 genes have been completely sequenced and are >99% identical at the DNA level across 41 exons and 15 kb of DNA. This high degree of homology and the presence of up to 3 C4 genes on any MHC haplotype makes PCR separation of the C4 genes difficult for subsequent genetic studies. The aim of this study was to extensively characterise the molecular heterogeneity of the human C4 genes and thereby: 1. determine the extent of human C4 gene polymorphism 2. confirm previous studies which have defined isotype specific sequences 3. characterise the C4 protein polymorphisms at the DNA level 4. determine if common C4 allotypes can be subtyped on a molecular basis 5. identify C4 gene polymorphisms that can be used as targets for DNA based typing methods 6. apply DNA based C4 typing methods in MHC disease association studies 7. provide insights into MHC haplotype evolution. In contrast to separating the C4 genes, a novel approach whereby the C4 genes were amplified and sequenced simultaneously was applied in this study. The DNA from 24 homozygous workshop cell lines, representing different ancestral haplotypes (AHs), was studied. Comparison of the C4 genes from different AHs revealed that the C4d region of the C4 a-chain is most polymorphic, but that polymorphic amino acid residues are also present in other regions of C4. The highest degree of polymorphisms was seen in the introns. In addition, the presence of the isotype specific sequences in exon 26 was confirmed and primers were designed to specifically amplify, and thereby separate, the C4A and C4B genes.Comparison of the C4 gene sequences representing the same C4 allotype revealed that most C4 allotypes are heterogeneous and may be split into several subtypes. The polymorphisms observed at the sequence level did not correlate with C4 allotypes defined by electrophoretic mobility. However, it could be shown that the differences in electrophoretic mobility of the C4 allotypes are due to cumulative charge differences. Seven polymorphic amino acids were found to account for the different migration rates of the C4 allotypes analysed in this study. In addition, a number of haplospecific single nucleotide polymorphisms (SNPs) were identified within the C4 genes. Haplospecific SNPs are informative markers enabling the genetic mapping of recombinant AHs, an approach which can be used to identify disease susceptibility genes. Haplospecific SNPs located in the C4 gene region are important markers as they represent a separate block of the MIIC (i.e. the gamma block). The frequency of one such SNP marker has been shown for a diabetes patient group and a control population. Although further studies are required to elucidate the role of the gamma block genes in susceptibility to diabetes, this study demonstrates a possible approach for the mapping of MHC disease susceptibility genes, which can also be applied in studies of other MHC associated diseases. To conclude, the present study adds to our knowledge of the C4 gene polymorphism, provides insights into MHC and C4 gene evolution and enables future studies to examine the significance of the C4 genes and other gamma block genes in susceptibility to MHC associated diseases.